2022
DOI: 10.34142/hsr.2022.08.04.01
|View full text |Cite
|
Sign up to set email alerts
|

Role of aerobics exercise and kettlebell training improving on selected health related physical fitness parameters in obese male adults

Abstract: Background: Aerobics exercise training and kettlebell training is recommended to prevent and control overweight/obesity.   Purpose: The aim of the this research is to assess the improvement in various variables related to health fitness among obese adults on administrating a twelve weeks aerobics exercise training and kettlebell training. Materials and Methods: Total sixty male adults with obese (Mean ± SD; age: 18.92 ± 1.54 yrs.; height: 172.4 ± 5.4 cm.; weight: 84.4 ± 6.3 kg) were randomly alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Regarding physiological variables, both the BWRTG and KRTG showed significant improvements in vital capacity, resting heart rate, breath holding time, and respiratory rate compared to the CG. The observed improvements in vital capacity, resting heart rate, breath holding time, and respiratory rate for both the body weight resistance training group and kettlebell training group are in line with previous research demonstrating the beneficial effects of exercise on various physiological parameters [ 39 , 55 ]. These improvements can be attributed to the adaptations of the cardiovascular and respiratory systems to regular exercise, which in turn result in better overall health and physical fitness [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding physiological variables, both the BWRTG and KRTG showed significant improvements in vital capacity, resting heart rate, breath holding time, and respiratory rate compared to the CG. The observed improvements in vital capacity, resting heart rate, breath holding time, and respiratory rate for both the body weight resistance training group and kettlebell training group are in line with previous research demonstrating the beneficial effects of exercise on various physiological parameters [ 39 , 55 ]. These improvements can be attributed to the adaptations of the cardiovascular and respiratory systems to regular exercise, which in turn result in better overall health and physical fitness [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 89%
“…These results align with the current body of the literature, which consistently supports the benefits of exercise on various health parameters [ 38 ]. The significant reductions in body mass and BMI for both BWRTG and KRTG can be attributed to the increased energy expenditure during exercise [ 39 ], leading to a negative energy balance and subsequent body mass loss [ 40 ]. Previous studies have also demonstrated the effectiveness of BWRTG for reducing body mass and the BMI, as it enhances cardiovascular fitness, muscular endurance, and overall physical capacity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ShapiroWilk test revealed that the assumptions of normality were met with the presented data [14]. Data are presented as mean and standard deviation (SD) [15].…”
Section: Discussionmentioning
confidence: 99%